2017
DOI: 10.1016/j.neuroimage.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional modular architecture underlying attentional control in aging

Abstract: Previous research suggests that age-related differences in attention reflect the interaction of top-down and bottom-up processes, but the cognitive and neural mechanisms underlying this interaction remain an active area of research. Here, within a sample of community-dwelling adults 19–78 years of age, we used diffusion reaction time (RT) modeling and multivariate functional connectivity to investigate the behavioral components and whole-brain functional networks, respectively, underlying bottom-up and top-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 124 publications
5
19
0
Order By: Relevance
“…An age-related decline in the rate of evidence accumulation in decisional processes (drift rate, v) has also been reported, though it is more task-dependent (Madden et al, 2009;Spaniol, Madden, & Voss, 2006;Yang, Bender, & Raz, 2015). Cautiousness, as reflected in the boundary separation parameter (a), also tends to increase with age (Ratcliff, 2008), though again with exceptions (Monge et al, 2017). Neuroimaging studies have found that age-related slowing of drift rate is associated with task-related frontoparietal activation and connectivity (Madden et al, 2010;Monge et al, 2017), but these previous studies did not isolate response-level processes.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…An age-related decline in the rate of evidence accumulation in decisional processes (drift rate, v) has also been reported, though it is more task-dependent (Madden et al, 2009;Spaniol, Madden, & Voss, 2006;Yang, Bender, & Raz, 2015). Cautiousness, as reflected in the boundary separation parameter (a), also tends to increase with age (Ratcliff, 2008), though again with exceptions (Monge et al, 2017). Neuroimaging studies have found that age-related slowing of drift rate is associated with task-related frontoparietal activation and connectivity (Madden et al, 2010;Monge et al, 2017), but these previous studies did not isolate response-level processes.…”
Section: Introductionmentioning
confidence: 88%
“…Cautiousness, as reflected in the boundary separation parameter (a), also tends to increase with age (Ratcliff, 2008), though again with exceptions (Monge et al, 2017). Neuroimaging studies have found that age-related slowing of drift rate is associated with task-related frontoparietal activation and connectivity (Madden et al, 2010;Monge et al, 2017), but these previous studies did not isolate response-level processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also found decreased degree values in the left inferior parietal lobule and left middle temporal gyrus were related to the cognitive function in the CCS-dependent individuals. A previous study demonstrated that the left inferior parietal lobule, one of the crucial brain regions of the attentional control network, was involved in executive function ( Monge et al, 2017 ). The current results suggested that such abnormal intrinsic connectivity may indicate cognitive and executive deficits in CCS-dependent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…When a non-spatial working memory task must be completed at the same time as visual search, search slows but search efficiency is unchanged (Oh & Kim, 2004;Woodman, Vogel, & Luck, 2001). Older adults also show slower search times, without increased display-size effects (Gorman & Fisher, 1998;Monge et al, 2017; see also Ratcliff, Thapar, & McKoon, 2006 for a similar increment in a discrimination task that is attributed to "nondecision" aspects of the task). Reduced capacity could be a factor in common between aging and dual tasking and may also explain our results, but note that this cannot be the same as general slowing since in MPS-IVa both simple RT and saccade onset times were either unaffected (saccade onset time) or only weakly affected (simple RT).…”
Section: Mps-iva (Morquio Syndrome)mentioning
confidence: 99%